CHENODEOXYCHOLIC ACID INHIBITS CFTR-MEDIATED CHLORIDE SECRETION IN RENAL TUBULAR CELLS - Soodvilai, Sunhapas; Srimai, Nipitpon (Thai Bulletin of Pharmaceutical Sciences, 2021)
Chenodeoxycholic acid (CDCA), a primary bile acid, has been reported to activate cystic fibrosis transmembrane conductance regulator (CFTR)-mediated Cl- secretion in intestinal cells. However, there have not been any reports on the role of bile acid in the regulation of CFTR-mediated Cl- secretion in renal cells. In this study, we revealed that CDCA reduced CFTR-mediated Cl- secretion in Madin-Darby canine kidney (MDCK) cells, renal tubular cells. Incubation MDCK cell monolayers with 20 µM CDCA for 48 h led to a decrease in [Arg8]-vasopressin (AVP)-induced Cl-current (ICl-). The inhibition on ICl- was not a result of CDCA-induced toxicity as shown by the treatment of the cells with CDCA for 72 h did not alter cell viability. Interestingly, acute incubation of MDCK cell monolayers with CDCA did not reduce ICl-. Furthermore, basolateral membrane permeabilization of MDCK cell monolayers still decreased apical ICl-, indicating that the target of CDCA might be located at the apical membrane. Western blot analysis revealed that inhibition of Cl- secretion occurred via a decrease in CFTR protein expression. These results reveal that CDCA inhibits Cl- secretion in renal tubular cells via a decrease in CFTR protein expression.